2 - The South African Experience with Developing and Implementing a Funding Formula for the Tertiary Education System: Pundy Pillay - Pundy Pillay, (Journal of Higher Education in Africa, 2004)
The funding framework developed in South Africa for institutions of higher edu- cation during the apartheid era raises serious concerns related to equity (access, particularly of the disadvantaged black majority) and efficiency (of outputs and outcomes, particularly, but not only, at historically black institutions). The new funding framework proposed in the government’s 1997 White Paper re- conceptualises the relationship between institutional costs and government expen- ditures. This framework is seen as a distributive mechanism to allocate govern- ment funds to individual institutions in accordance both with the budget made available by government and with government’s policy priorities. Institutions now receive (a) block funds (research funds, teaching funds determined by student num- bers and outputs, and institutional funds for redress purposes), and (b) earmarked funds for specific purposes (e.g., student financial aid and research development). This framework has important implications for equity and efficiency including predictability; the recognition of a hard budget constraint; promoting institutional autonomy and equity; rewards for research outputs; rewards for graduate outputs that supply the country’s human development needs; and enhanced equity through capacity building, research development, and foundation programmes.